Response of Peking Shallot (Allium ascalonicum L.) to Dolomite and Granular Guano Application on Recovered Lowland Ultisol by Goat Manure - Resigia, Elara; Kristina, Nilla (Kadiri University - Faculty of Agriculture, 2025)
Shallots are essential for Indonesia's economy and food security. In West Sumatra, cultivating shallots in the highlands is more challenging than in the lowlands. Lowland areas have poor Ultisol soil, but its chemical properties can improve with cultivation. Using organic materials, such as goat manure and granular guano with dolomite, is one solution to this problem. Unfortunately, shallot farmers often apply excessive amounts of dolomite. The ideal dosage of guano and dolomite as calcium, phosphorus, potassium, and magnesium sources must be determined for optimal shallot growth. Using goat manure may reduce the need for other inputs like dolomite. Guano and dolomite combination treatments have never been used on Peking shallot varieties grown on Ultisol soil. This study evaluated the growth and yield responses of Peking variety shallots to dolomite and guano applications on Ultisol soil improved with goat manure as a base fertilizer. The experimental design was two-factorial, completely randomized, with three replications. The first factor was the dolomite dose, with three levels: 0, 2, and 4 tons/ha. The second factor was the dose of granulated guano, with four levels: 0, 100, 200, and 300 kg/ha. All experimental units received goat manure-based fertilizer at a dose of 10 tons/ha. Data were analyzed with ANOVA at 5% confidence, then with Duncan's Multiple Range Test if the treatment had a significant effect. The results showed that applying dolomite and granulated guano did not significantly affect the growth parameters or yield of Peking variety shallots.